An investigation of industrial molding compounds for use in 3D ultrasound, MRI, and CT imaging phantoms. Issue 5 (26th April 2013) - Yunker, Bryan E.; Cordes, Dietmar; Scherzinger, Ann L.; Dodd, Gerald D.; Shandas, Robin; Feng, Yusheng; Hunter, Kendall S.
Abstract : Purpose: : This study investigated the ultrasound, MRI, and CT imaging characteristics of several industrial casting and molding compounds as a precursor to the future development of durable and anatomically correct flow phantoms. Methods: : A set of usability and performance criteria was established for a proposed phantom design capable of supporting liquid flow during imaging. A literature search was conducted to identify the materials and methods previously used in phantom fabrication. A database of human tissue and casting material properties was compiled to facilitate the selection of appropriate materials for testing. Several industrial casting materials were selected, procured, and used to fabricate test samples that were imaged with ultrasound, MRI, and CT. Results: : Five silicones and one polyurethane were selected for testing. Samples of all materials were successfully fabricated. All imaging modalities were able to discriminate between the materials tested. Ultrasound testing showed that three of the silicones could be imaged to a depth of at least 2.5 cm (1 in.). The RP‐6400 polyurethane exhibited excellent contrast and edge detail for MRI phantoms and appears to be an excellent water reference for CT applications. The 10T and 27T silicones appear to be usable water references for MRI imaging. Conclusions: : Based on study data and the stated selection criteria, the P‐4 silicone provided sufficient material contrast to water and edge detail for use across all imaging modalities with the benefits of availability, low cost, dimensional stability, nontoxic, nonflammable, durable, cleanable, and optical clarity. The physical and imaging differences of the materials documented in this study may be useful for other applications.